Contribution to the Taking into Account of Environmental Factors of Vulnerability of Reinforced Concrete Buildings in the City of Douala-Cameroon - Langola Olivier; Abanda André; Lontsi Frédéric; Kom Charles (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
The environment of the city of Douala (humid, porous, sandy-clay soil), plays a determining role on the vulnerability of reinforced concrete constructions, by effects of corrosion of degradations, and destructions of the structures (buildings). Relative Y, the method tree of the causes and the tests pH-metric, granulometric and permeameters , allowed us to seek, to check and to analyze certain environmental factors impacting on the constructions, weakening the concrete and pari cochet , the resistance and the durability of the buildings. To this end, the pH tests of groundwater, springs and industrial discharges, containing chloride ions (Cl-), sulphates and carbon dioxides from heavy rainfall and flooding, attack by an electrochemical mechanism the reinforcement and framework of the constructions. Thus, the results obtained from the tests, demonstrate how the dangerous acids present in water, penetrate into the reinforced concrete to destroy it. The resulting chemical reaction of hydration absorbs the water and swells the concrete to reach the steel, weakening it and destroying the protective film (passivation). The action of water on concrete is declined by absorption, hydrolysis, dissolution, solvation and crystallization. Also, the corrosion rate of materials remaining strongly inherent to the high humidity and PH level ? 6, directly influencing the electrical resistivity conductivity and diffusion of oxygen and carbon dioxide in concrete. As such, the relative humidity (RH) or high water content in concrete and the environment of the site receiving the construction project, produces permeability decreasing effects in the presence of oxygen. These effects contribute to stimulate and increase the corrosion process. Because, water, soil and industrial pollutants, affect the works Given, that it is demonstrated that a quasi-permanent moisture content ? 55% in a porous material such as concrete, leads to the loss of 20 to 30% of its cohesion. Hence, the various forms of degradation and loss of loads suffered by the constructions. To this end, the binder content, mineral additives and the water/cement ratio (W/C), are to be considered for the evaluation, resistance and durability of the constructions. Also, most of the methods used to determine the permeability of porous materials are based on Darcy’s law. This is because, in its basic form, the fluid flows through a disc-shaped sample under a pressure gradient. Consequently, in addition to the requirement of carrying out geotechnical studies of materials and soil in accordance with the standards of construction and urban planning, pH metric tests are necessary for the effective consideration of environmental factors to achieve the resilience and durability of reinforced concrete structures. It will be in particular: ( i ) to identify and analyze the impacts of water and soil on reinforced concrete constructions; (ii) to verify and analyze the compliance of the said constructions with the geotechnical and urban planning standards (realization of geotechnical studies and the use of adequate quality materials and qualified manpower); (iii) to contribute to the considerable reduction of the vulnerability of the works to the attacks of the sulphates , for a better safety and durability of the constructions.